2014
DOI: 10.1016/j.autrev.2014.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset Still's disease

Abstract: First described in 1971, adult-onset Still's disease (AOSD) is a rare multisystemic disorder considered as a complex (multigenic) autoinflammatory syndrome. A genetic background would confer susceptibility to the development of autoinflammatory reactions to environmental triggers. Macrophage and neutrophil activation is a hallmark of AOSD which can lead to a reactive hemophagocytic lymphohistiocytosis. As in the latter disease, the cytotoxic function of natural killer cells is decreased in patients with active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
562
2
43

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(621 citation statements)
references
References 205 publications
14
562
2
43
Order By: Relevance
“…Recent studies have shown that inflammatory cytokines, including interleukin (IL)-1, IL-6, IL-18, interferon (IFN)-γ, and tissue necrosis factor (TNF)-α play pathogenic roles in the disease processes of both s-JIA and AOSD [12,13]. Furthermore, biological therapies intended to block these cytokines yield dramatic effects in patients with s-JIA and AOSD [14,15].…”
mentioning
confidence: 99%
“…Recent studies have shown that inflammatory cytokines, including interleukin (IL)-1, IL-6, IL-18, interferon (IFN)-γ, and tissue necrosis factor (TNF)-α play pathogenic roles in the disease processes of both s-JIA and AOSD [12,13]. Furthermore, biological therapies intended to block these cytokines yield dramatic effects in patients with s-JIA and AOSD [14,15].…”
mentioning
confidence: 99%
“…Adult-onset Still's disease (AOSD) generally affects children or young adults, and also was described up to 83 years (1). The etiology of AOSD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…and environmental factors such as infections (Epstein-Barr virus, hepatitis B and C virus, human immunodeficiency virus, yersinia enterocolitica etc.) have been suspected in the pathogenesis (1). Hemophagocytic syndrome (HS) is also a rare disorder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations